DEVELOPING FILMS TO SUPPORT THE TEACHING AND LEARNING OF THE COURSE “TOY MAKING SKILLS FOR PRESCHOOL CHILDREN” - Pham Thi Bich Huyen (Tạp chí Khoa học)
This research focuses on developing an instructional video to support teaching and learning the “Skills in Making Toys for Preschoolers” course within the preschool teacher training program. The research results have established a process for creating instructional videos, which includes key issues such as the goals, principles, and content of the instructional video for the Toy-making Skills course. The result helps lecturers and students conduct teaching and learning activities lively and engagingly. Notably, it has successfully stimulated students' interest in learning, meeting the demands of innovation in teaching and learning the Skill of Toy Making in the era of the 4th Industrial Revolution.